Nanocellulose from Diseased Coconut Wood Biomass - Jayaraj, A. P.; Ravindranath, Anita Das; Sarma, U. S. (International Coconut Community Journal, 2014)
Cellulose is the most widespread biopolymer on earth. In biosynthesis, cellulose polymers aggregate to form substructures, microfibrils, which in turn aggregate to form cellulose fibers. By applying effective methods these fibers can be disintegrated into cellulose substructures with micro- or nano-size dimensions. This article covers some aspects related to the sources of cellulose micro- and nanofibers and the most important methods for their isolation. One of these methods, acid hydrolysis, was experimentally used to obtain cellulose nano-fibers from diseased coconut wood biomass. They were studied by Thermogravimetric analysis (TGA), X-ray diffractometer (XRD) and Scanning electrom microscope (SEM). The ‘Replanting and Rejuvenation of Coconut Gardens’ was the sponsored scheme of the Coconut Development Board with an objective to eliminate all disease- affected coconut palms in eight districts of Kerala state in India. The main components of the scheme included cutting and removal of all old, unproductive and disease-hit palms followed by a replanting exercise. The present work was carried out under the Board sponsored project entitled “Diversified uses of diseased coconut wood”.